PEMECAHAN MASALAH DALAM PEMBELAJARAN MATEMATIKA MELALUI PROBLEM POSING - Tedy Machmud (Jurnal Inovasi, 2009)
One of the ways that the teacher can do to give students experience in mathematics is by Problem posing. Problem posing can be means as reformation or reformulation of the tests by the students or by the teacher. Problem posing is one thing that should get a big attention in mathematics teaching. Teacher is an important element to increase the students ability to form the test or the questions. Problem posing should be introduced to the students, because by having the skills to form the test or the questions the students can be creative, smart, responsible also they can solve the problem that they will find.